2015
DOI: 10.1007/s00216-015-8858-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in quantitative LA-ICP-MS analysis: challenges and solutions in the life sciences and environmental chemistry

Abstract: Laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) is a widely accepted method for direct sampling of solid materials for trace elemental analysis. The number of reported applications is high and the application range is broad; besides geochemistry, LA-ICP-MS is mostly used in environmental chemistry and the life sciences. This review focuses on the application of LA-ICP-MS for quantification of trace elements in environmental, biological, and medical samples. The fundamental problems of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
181
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(208 citation statements)
references
References 173 publications
(304 reference statements)
3
181
0
1
Order By: Relevance
“…Various calibration strategies for LA-ICP-MS have been reported and applied to the analysis of geological, environmental, biological, and medicine samples. [1][2][3][4][5][6] However, there is not a single calibration strategy covering all kinds of samples. Therefore, improvement of calibration strategies for LA-ICP-MS is still required for quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Various calibration strategies for LA-ICP-MS have been reported and applied to the analysis of geological, environmental, biological, and medicine samples. [1][2][3][4][5][6] However, there is not a single calibration strategy covering all kinds of samples. Therefore, improvement of calibration strategies for LA-ICP-MS is still required for quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-ablation (LA) sample introduction is an effective tool to elucidate elemental compositions in solid materials with ICP-MS. 1 Nakazawa et al reported on "Acceleration of Vaporization, Atomization, and Ionization Efficiencies in Inductively Coupled Plasma by Merging LaserAblated Particles with Hydrochloric Acid Gas". They improved vaporization, atomization, and ionization efficiencies of elements in a glass material by merging ablated particles with HCl gas.…”
mentioning
confidence: 99%
“…[1][2][3] However, its main analytical problem lies in the calibration step. 4 In fact, standards used for external calibration should be closely matrix matched to the sample. In some instances, the elemental fractionation caused during aerosol formation, its transport to the ICP and the analyte vaporization and ionization in the ICP plasma leads to inaccurate results.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the preparation of matrix matched standards can be time consuming, expensive. [4][5][6][7] and it may degrade the spatial integrity of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation